2020
DOI: 10.3390/jcm9113562
|View full text |Cite
|
Sign up to set email alerts
|

The Wearable VOSTARS System for Augmented Reality-Guided Surgery: Preclinical Phantom Evaluation for High-Precision Maxillofacial Tasks

Abstract: Background: In the context of guided surgery, augmented reality (AR) represents a groundbreaking improvement. The Video and Optical See-Through Augmented Reality Surgical System (VOSTARS) is a new AR wearable head-mounted display (HMD), recently developed as an advanced navigation tool for maxillofacial and plastic surgery and other non-endoscopic surgeries. In this study, we report results of phantom tests with VOSTARS aimed to evaluate its feasibility and accuracy in performing maxillofacial surgical tasks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 40 publications
1
36
0
Order By: Relevance
“…Various methods have been proposed in the literature to automatically align virtual content to a target anatomy. A highly accurate overlay of virtual content was demonstrated in [ 20 ], using fiducial markers and a custom head-mounted display. The authors reported an error below 1 mm in a maxillofacial surgical task conducted on plastic bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods have been proposed in the literature to automatically align virtual content to a target anatomy. A highly accurate overlay of virtual content was demonstrated in [ 20 ], using fiducial markers and a custom head-mounted display. The authors reported an error below 1 mm in a maxillofacial surgical task conducted on plastic bone.…”
Section: Discussionmentioning
confidence: 99%
“…Research in this topic is ongoing, and several methods have been proposed (e.g., [ 22 , 23 ]) to increase the accuracy of general-purpose headsets currently available on the market. Additionally, various companies and research groups have worked on the development of bespoke head-mounted displays, specifically tailored to the needs of intraoperative surgical guidance, e.g., [ 20 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The subsequent step toward further evolution in the preoperative study of the patient concerns the adoption of AR, a technology destined to revolutionize image-guided surgery, but which still suffers from many inaccuracy biases and thus still very limited in its clinical application (8,(23)(24)(25). To make a step forward, we applied AR in the pre-operative study of the case, using a 3D printed phantom of the skull of the patient, merged with the animated planning exported from the animation software.…”
Section: Discussionmentioning
confidence: 99%
“…The technology could also become part of the surgical workflow, where the possible advantages can disrupt surgical outcomes in various surgical specialties since it complements and integrates the concepts of standard surgical navigation based on virtual reality. In the literature, AR HMDs have been used to visualize the 3D anatomy of the patient overlaid onto the surgical field, in order to guide the alignment of bony structures, and in some case to actually guide the surgical gestures [34][35][36].…”
Section: Discussionmentioning
confidence: 99%